2023
DOI: 10.3389/fcell.2023.1105692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold atmospheric microwave plasma (CAMP) on wound healing in canine keratinocytes

Abstract: Cutaneous wound healing is a biological process that occurs upon skin injury and involves different mechanisms to repair tissue damage. Improper healing or prolonged curation period of wound lesions may induce unpleasant complications. Cold atmospheric microwave plasma (CAMP) is an upcoming medical therapeutic option for skin infection and wound treatment. However, the molecular mechanisms of CAMP-mediated canine wound healing are not well characterized. Wound-healing activity was examined to elucidate the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Previous work showed that YAP1 nuclear localization in adherent HaCaT cultures is dependent on cell density [24] , that YAP1 activity is primarily confined to the basal, proliferating keratinocyte layer of the epidermis [43] , and that YAP1 activity is increased in activated keratinocytes during wound healing [44] . This prompted us to investigate a potential correlation between the reduced amount of Ki-67+ HaCaT cells in spheroids from plate type A.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work showed that YAP1 nuclear localization in adherent HaCaT cultures is dependent on cell density [24] , that YAP1 activity is primarily confined to the basal, proliferating keratinocyte layer of the epidermis [43] , and that YAP1 activity is increased in activated keratinocytes during wound healing [44] . This prompted us to investigate a potential correlation between the reduced amount of Ki-67+ HaCaT cells in spheroids from plate type A.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on wound healing and cancer cell treatment with CAP describe the characteristics of the plasma generator and treatment conditions, and report the effects of different plasma treatment conditions. In wound healing treatments using animal models, the operating voltage for plasma generation ranges from 7 to 32 kV, and the SLM ranges from 0.5 to 5.0 l min −1 (figure 1(G)) [121][122][123][124][125]. Ar is predominantly used as the CAP gas, but He, O 2 , N 2 or a mixture of these has also been utilized [38,94,[126][127][128] He-CAP effectively coagulates blood vessels in wound tissues, and new blood vessels form better in plasma-irradiated tissues than in non-plasma-treated tissues [37].…”
Section: Comparing Cap Application Conditions Between Wound Healing A...mentioning
confidence: 99%
“…[42] Cold atmospheric microwave plasma-treated cells indicate the downregulation of E-cadherin and upregulation of vimentin, Snail, and Slug at transcription and translation levels, thereby promoting cell migration. [63] These cells promote the cytoskeletal transformation of keratinocytes and migration due to changes in the expression of integrin-dependent focal adhesion molecules and MMPs. [64]…”
Section: Proliferative Phasementioning
confidence: 99%